Team dimension of relational competence in organization ? psychological perspective = Zespołowy wymiar kompetencji relacyjnej organizacji ? ujęcie psychologiczne - Kożusznik, Barbara; Chrupała-Pniak, Małgorzata; Sulimowska-Formowicz, Monika (Zielona Góra: Faculty of Economics and Management Press)
This article is a part of theoretical model for the research project titled ?Relational competence as a determinant of effectiveness and efficiency of inter-organizational relations?. The authors deliberate upon team-level determinants of relational competence of organizations involved in inter-organizational cooperation in the light of classic and modern psychological theories and concepts.
Keywords: kompetencje relacyjne; cechy zespołu; regulacja wpływu; relational competence; team characteristics; influence regulation